High expression of MRPL52 can be used as a prognostic marker of hepatocellular carcinoma and is related to immune infiltration - Nan HUANG; Xiang LIU; Qichang XING; Jia CHEN; Xiaolan GUO; Wei LI; Zheng LIU (Journal of Holistic Integrative Pharmacy)
Objective: To analyze the differential expression and prognostic value of Mitochondrial ribosomal protein L52 (MRPL52) in hepatocellular carcinoma using bioinformatics, and to explore the prognostic value and role of the MRPL52 in the immune regulation of hepatocellular carcinoma. Methods: Hepatocellular Carcinoma Database (HCCDB) and Tumor Immune Estimation Resource (TIMER) databases were used in analyzing the differential expression of MRPL52 in hepatocellular carcinoma tissue and normal paracancerous tissues; UALCAN database was used to analyze the correlation between levels of MRPL52 expression and levels of DNA methylation vs. clinical phenotypes, including tumor grade, tumor stage, and metastasis, Kaplan–Meier plotter database was used in analyzing the relationship between MRPL52 expression and hepatocellular carcinoma survival; LinkedOmics database was used in analyzing MRPL52 co-expression genes, target miRNAs and transcription factors; GENEMANIA database was used to construct the protein interaction network; DiseaseMeth database and MEXPRESS database were used to analyze the level of MRPL52 DNA methylation and changes in methylation sites, and TIMER database was used in analyzing the relationship between MRPL52 and immune infiltration of hepatocellular carcinoma. Results: MRPL52 was highly expressed in hepatocellular carcinoma and was positively correlated with clinical phenotypes, including tumor grade, tumor stage, and distant metastasis; high expression of MRPL52 was associated with poor prognosis of hepatocellular carcinoma; co-expression analysis showed that MRPL52 co-expression genes were enriched in multiple cancer-related signal pathways, and methylation analysis showed that the DNA methylation level of MRPL52 reduced significantly in hepatocellular carcinoma. Additionally, significant changes were found in methylation sites cg07436208 and cg04556361, which were negatively correlated with the expression level of MRPL52, and K–M survival analysis showed that the cg04556361 methylation site was negatively correlated with the overall survival of hepatocellular carcinoma; MRPL52 was associated with immune cell infiltration of hepatocellular carcinoma, and Cox multivariate regression analysis showed that MRPL52 could increase the risk of overall survival (OS) by 1.435-fold in the absence of immune cells. Conclusion: The expression level of MRPL52 in patients with hepatocellular carcinoma is increased, which is related closely to poor prognosis, suggesting that MRPL52 is expected to become a prognostic marker and a new target for the treatment of hepatocellular carcinoma.